2016
DOI: 10.1177/0952076715625104
|View full text |Cite
|
Sign up to set email alerts
|

Partnership working in sport and physical activity promotion: An assessment of processes and outcomes in community sports networks

Abstract: Community sports networks were established in 2007 to coordinate local sport and physical activity promotion. Partnerships continue to be used to deliver policy. It is important to understand the relationship between the internal structure of partnerships and their outcomes. This study assesses associations between predictor variables relating to partnership structure and process and four intermediary partnership outcomes: satisfaction, synergy, commitment and effectiveness. A retrospective analysis of data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…al. (2016) found similar results stating that sustaining a positive benefits‐to‐costs relationship, establishing effective communication and partnership strategy, and demonstrating impact were predictive of the four intermediary partnership outcomes 30 . Aligned with our findings, Baker also found that selecting a public organisation or a social cause that “fit” with their resources and mission a challenge for private‐sector participation in community and charitable activities 30 .…”
Section: Discussionsupporting
confidence: 81%
“…al. (2016) found similar results stating that sustaining a positive benefits‐to‐costs relationship, establishing effective communication and partnership strategy, and demonstrating impact were predictive of the four intermediary partnership outcomes 30 . Aligned with our findings, Baker also found that selecting a public organisation or a social cause that “fit” with their resources and mission a challenge for private‐sector participation in community and charitable activities 30 .…”
Section: Discussionsupporting
confidence: 81%
“…None of the PPP initiatives in this review reported the partnership type, yet we can speculate partnership types based on the strength of the partnership and the level of integration between the partners reported in some of the articles. As partnership type is one essential component in planning how to manage partnership activities (Baker et al, 2017;Brinkerhoff & Brinkerhoff, 2011), defining the partnership types is suggested in future initiatives to promote physical activity. On a related note, there is also a lack of reporting on the effectiveness of PPP in actually promoting physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…There are different types of PPPs based on the strength of the relationship between the partners, the level of integration of the resources and activities, and the decision-making power. When a government or a public-sector organization seeks expert input and financial support in a noncollaborative manner from the private for-profit sector, the public partner has a dominant power in decision-making as well as the major responsibility for the implementation of the interventions (Baker, Ansari, & Crone, 2017). In this case, the private partner acts as a donor who executes philanthropic activities, in which they contribute cash or in-kind without any specific expectation of a tied benefit.…”
Section: Types Of Pppsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in line with the existing body of knowledge on health promotion partnerships, which describes working in partnerships as a multifaceted process influenced by (a) the institutional and personal backgrounds and differences therein that are brought into the partnership and (b) how the partnership is governed (e.g., . Furthermore, it confirms evidence from a recent quantitative study by Baker et al (2017) showing that a large variety of partnership elements, including leadership, communication, and trust, correlate with synergy in sport-for-health partnerships.…”
Section: Discussionsupporting
confidence: 85%